1989
DOI: 10.1144/gsjgs.146.2.0305
|View full text |Cite
|
Sign up to set email alerts
|

The stratigraphic and palaeogeographic setting of the late Cenomanian ‘anoxic’ event

Abstract: The late Cenomanian carbon isotope excursion can be shown to be synchronous over most areas of the globe where micropalaeontological data are adequate. The sedimentological variations seen in these different areas are thought to be due to palaeobathymetry. The relationship between this 'anoxic' event and the major faunal change in the late Cenomanian is described.In a recent review of 'anoxic events ', Funnell (1987) has questioned (1) how anoxic, anaerobic or dysaerobic such events were, and ( 2 ) how localiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…The lower is in the uppermost Cenomanian, a well-known and widespread source rock interval throughout the Atlantic (de Graciansky et al 1987;Hart & Leary 1989) and locally reported from Wells 6506/12-4 and 35/3-5. The upper is in the Campanian, reported from Wells 6507/2-1 and 6607/5-1.…”
Section: Late Cretaceousmentioning
confidence: 88%
“…The lower is in the uppermost Cenomanian, a well-known and widespread source rock interval throughout the Atlantic (de Graciansky et al 1987;Hart & Leary 1989) and locally reported from Wells 6506/12-4 and 35/3-5. The upper is in the Campanian, reported from Wells 6507/2-1 and 6607/5-1.…”
Section: Late Cretaceousmentioning
confidence: 88%
“…They dominate the planktonic assemblages from the R. cushmani and the H. helvetica TRZ, which are periods characterized by welloxygenated water with low nutrient levels allowing a specific diversification and the development of more sophisticated morphotypes (Grosheny and Malartre, 1997;Caron et al, 2006;Mort et al, 2007). The second group is composed of globular trochospiral and biserial forms with small and simple morphotypes (e.g., Whiteinella and Heterohelix), which mainly lived in the upper-water column with high nutrient levels (Hart and Leary, 1989;Petters, 1980;Jarvis et al, 1988;Grosheny and Malartre, 1997;Leckie et al, 1998;Keller and Pardo, 2004). They are interpreted as r-selected species (MacArthur and Wilson, 1967) and date from the W. archaeocretacea PRZ.…”
Section: Planktonic Foraminifera As Environmental Proxiesmentioning
confidence: 99%
“…Distinct intervals of black shale deposition with unusually high concentrations of total organic carbon (TOC) termed oceanic anoxic events (OAE) were deposited on a global scale during the Aptian-Albian, Cenomanian-Turonian and Coniacian-Santonian (e.g., Hart and Leary, 1989;Crowley, 1991;Johnson et al, 1996;Wilson et al, l998;Jones and Jenkyns, 2001;Norris et al, 2002;Leckie et al, 2002). At these times, the sequestration of the organic carbon due to high burial rates favored the formation of petroleum source rocks and reduced atmospheric PCO 2 , which affected climate (e.g., Kuypers et al, 1999;Kolonic et al, 2005).…”
Section: Introductionmentioning
confidence: 99%